The Role of Forum Membership Diversity on Institutional Externalities in Resource Governance Systems. Issue 11 (2nd November 2019) - Mewhirter, Jack; McLaughlin, Danielle M.; Fischer, Manuel
Abstract: In many resource governance systems, representatives of resource-related organizations gather in forums to discuss and develop solutions to policy problems. Forums often deal with interdependent policy problems, giving rise to institutional externalities: instances where decisions made in one forum either decrease (negative institutional externality) or increase (positive institutional externality) the rate by which current policy outputs in other forums resolve their prescribed policy problems. In this article we argue that forum-specific factors can impact the direction of such externalities. We theorize that forums with more diverse memberships in terms of both the issues that participants care about and types of organizations represented are better equipped to incorporate more holistic, ecosystem-based perspectives, which promote the generation of positive institutional externalities. Our study utilizes survey data collected from forum participants in the California Delta. Results from a series of cross-nested regressions demonstrate a positive association between forum diversity and positive externalities.